Is nasal airflow disrupted after endoscopic skull base surgery? A short review - Májovský, M; Trnka, F; Schmirlerová, H; Betka, J; Hyhlík, T; Netuka, David (Neurosurgical review, 2022)
Even the most delicate endonasal surgery for skull base lesion causes changes in the nasal cavity, some of them permanent. Morphological changes in the nasal cavity and their consequences (changes in nasal airflow) are often studied by advanced numerical analysis called computational fluid dynamics. This review summarizes current knowledge of endoscopic transsphenoidal skull base surgery effects on nasal airflow. Several studies have shown that endoscopic skull base surgery changes nasal anatomy to the extent that nasal airflow changes significantly postoperatively. Removing any intranasal structure increases the cross-sectional area of the respective nasal meatus, leading to increased nasal airflow in this area while airflow in the narrower periphery decreases. Middle turbinate resection increases airflow in the middle meatus and reduces airflow in the superior and inferior meatus. Small posterior septectomy does not cause a significant change in nasal airflow. Nasal septum deviation is an important factor in airflow changes. Current studies describe nasal changes after rather extensive procedures (e.g., middle turbinectomy, ethmoidectomy) that are unnecessary in routine pituitary adenoma surgery. No studies have compared changes using pre- and postoperative scans of the same patients after actual surgery.
Keywords: nosní dutina; nosní skořepy; Nasal Septum; Olfaction; Endoscopic surgery; Skull Base; Computational fluid dynamics; Turbinates; Nasal Cavity; endoskopie; Endoscopy; lidé; Skull base; Transsphenoidal approach; baze lební; nosní přepážka; Humans; Nasal airflow